SMALL-SCALE HETEROGENEITY AT THE TOP OF THE LOWER MANTLE AROUND THE MARIANA SLAB - Kaneshima S. (My University, 2003)
Short-period waveform data recorded at the western US seismic array for 14 Mariana deep earthquakes near 19°N show two anomalous wave packets within about 30 s after the arrival of the direct P-wave (simply called 'P' or 'P-wave'): one at about 13 s (called 'X1 phase') and the other around 29 s (called 'X2 phase'). We perform array analyses to locate the sources of these phases. In the first step, we measure arrival time, slowness, back-azimuth, and amplitude of these phases relative to P. The amplitudes of the X1 and X2 phases correlate with each other for the individual events, and vary more than an order of magnitude among the events which cluster in a region spanning less than 50 km. The amplitude correlation suggests that the two waves have a similar origin, and the large amplitude variation eliminates receiver side reverberation as the origin of the phases. The X1 phase has a slowness and an arrival azimuth which are not distinguished from those of P-waves across the entire array, and has nearly constant delay times regardless of the focal depths (from 567 to 605 km). The X2 phase arrives as a more emergent wave packet with slowness and azimuth different from those of P. In the second step, we compute composite semblance coefficients for the cases of P-to-P and S-to-P single scattering near the foci. The X1 and X2 phases are best interpreted as S-to-P scattered waves generated in the uppermost lower mantle north of the focal region based on three observations: (1) highest composite semblance values, (2) scatterer locations mutually consistent between the two event groups near the depths of 500 and 600 km, and (3) a reasonable amount of elastic property anomalies required. The X1 phase scatterer is determined at 19.8°+/-0.3°N, 145.7°+/-0.3°E, 710+/-30 km. On the other hand, the scatterer of the X2 phase appears to split into two objects: one at 20.4°+/-0.4°N, 145.4°+/-1.0°E, 900+/-80 km, and the other at 20.6°+/-0.4°N, 147.4°+/-0.5°E, 860+/-40 km. Although the geometries of the scatterers of X1 and X2 phases are not constrained, horizontal or subhorizontal discontinuities are unlikely. The changes in elastic properties associated with these heterogeneous objects probably occur within several kilometers, according to their high efficiency at converting short-period waves. They are thus likely to represent sharp chemical variations in major element composition. These objects are located within a thickened high-velocity anomaly at the top of the lower mantle, which has been determined by previous seismic studies. A plausible tectonic interpretation of these objects is that they are fragments of former oceanic crust which are entrained in the Pacific slab impinging on the more viscous lower mantle.
Keywords: TOP OF THE LOWER MANTLE; SMALL-SCALE HETEROGENEITY; S-TO-P WAVE SCATTERING; SEISMIC ARRAY ANALYSES; FORMER OCEANIC CRUST